Synthesis of hydroxyapatite powder from mollusc shell - Koonawoot R. (2014)
Synthesis hydroxyapatite (HA) powders from mollusc shell with the solid solution reaction method. The process is a new method which makes the amount of HA powder in large quantities. The advantage of the solid state method which involves molar ratio of calcium and phosphorus through a thermal treatment and reaction time, caused by the diffusion of ions in the solid particles. HA is the only apatite present in the reaction products, apart from minute fractions of certain other calcium compounds. The final product is characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and fourier transform infrared (FTIR). © (2011) Trans Tech Publications, Switzerland.